Legal Protection for Group III State House Buyers in Flawed Ownership Transfer Agreements - Nur, Thursina Megah Rizqa Aulia; Djumikasih, Djumikasih; Widhiawati, Dyah (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
This research addresses the urgent issue of legal uncertainty faced by buyers of Class III state-owned houses who enter into ownership transfer agreements that are procedurally flawed. Despite fulfilling their financial obligations, many buyers encounter administrative and legal challenges due to unclear regulations and improper transfer procedures. Using a normative legal research approach, this study applies statutory and conceptual methods to evaluate the legal status of such agreements and the extent of state responsibility in protecting buyers’ rights. The findings indicate systemic weaknesses, including the absence of authentic deeds, lack of oversight by authorized officials, and inconsistencies in house classification and approval processes. These issues severely undermine the legal position of buyers and expose them to risks of dispute and asset loss. The study highlights the need for comprehensive legal reform to ensure both preventive protection—through clearer regulatory guidelines—and repressive protection—through access to judicial remedies. The novelty of this research lies in its focus on Class III state housing, a topic rarely examined in-depth in Indonesian legal scholarship. To strengthen legal certainty and uphold citizens’ constitutional right to adequate housing, the study recommends revising existing regulations, institutionalizing oversight mechanisms, and improving public legal awareness.